Evaluation of single-fraction high dose FLASH radiotherapy in a cohort of canine oral cancer patients - Børresen, Betina; Arendt, Maja L.; Konradsson, Elise; Bastholm Jensen, Kristine; Bäck, Sven ÅJ.; Munck af Rosenschöld, Per; Ceberg, Crister; Petersson, Kristoffer (Frontiers in Oncology, 2023)
Background: FLASH radiotherapy (RT) is a novel method for delivering ionizing radiation, which has been shown in preclinical studies to have a normal tissue sparing effect and to maintain anticancer efficacy as compared to conventional RT. Treatment of head and neck tumors with conventional RT is commonly associated with severe toxicity, hence the normal tissue sparing effect of FLASH RT potentially makes it especially advantageous for treating oral tumors. In this work, the objective was to study the adverse effects of dogs with spontaneous oral tumors treated with FLASH RT. Methods: Privately-owned dogs with macroscopic malignant tumors of the oral cavity were treated with a single fraction of ³30Gy electron FLASH RT and subsequently followed for 12 months. A modified conventional linear accelerator was used to deliver the FLASH RT. Results: Eleven dogs were enrolled in this prospective study. High grade adverse effects were common, especially if bone was included in the treatment field. Four out of six dogs, who had bone in their treatment field and lived at least 5 months after RT, developed osteoradionecrosis at 3-12 months post treatment. The treatment was overall effective with 8/11 complete clinical responses and 3/11 partial responses. Conclusion: This study shows that single-fraction high dose FLASH RT was generally effective in this mixed group of malignant oral tumors, but the risk of osteoradionecrosis is a serious clinical concern. It is possible that the risk of osteonecrosis can be mitigated through fractionation and improved dose conformity, which needs to be addressed before moving forward with clinical trials in human cancer patients.